YOUNG COMIC BOOK’S FANS IN FRANCE AND THEIR CREATION ON INTERNET - JANKEVIČIŪTĖ, LAURA (Knygotyra, 2015)
The digital age greatly expanded the possibilities for participation and expression. The digital revolution impacted cultural participation and placed fan culture in a new light. It touched the books’ fans who were looking for new ways of expressing themselves and their passion. Inspired by the stories and the characters of their favorite books, the fans began to produce the new narrative forms named fanfictions and to offer original stories’ extensions or new versions, to publish these creations on the special fanfictions’ websites. An opportunity to publicize these texts, to receive the comments and other type of reaction, to discuss and share different opinions attracted a considerable interest. Not all new forms of expression have gained ground in the dynamic digital culture, but the fanfictions are still popular among the fans. Among others, it fascinates young comic books’ readers and fans in France. This article analyzes one of the digital youth culture’s forms. Particular attention is given to the digital expressiveness, which promotes new forms of expression among different social groups. Focusing on the fan culture, the ability to modify culture and the new creative fan art forms encouraged by digital revolution are discussed. Based on the results of the study, conducted in two public schools of the city of Bordeaux (France), the process of fanfictions’ writing and reading among young comic books fans is analysed.
Keywords: ...